Case study of an MBT plant producing SRF for cement kiln co-combustion, coupled with a bioreactor landfill for process residues. (January 2016) - Grosso, Mario; Dellavedova, Stefano; Rigamonti, Lucia; Scotti, Sergio
Highlights: Performances of an innovative energy recovery pathway from the residual waste are described. Peculiar of the analysed system is the disposal of MBT residues in a bioreactor landfill. An LCA of the system is presented based on one year operational data. Abstract: The paper describes the performances of the energy recovery pathway from the residual waste based on the production of a Solid Recovered Fuel (SRF) to be exploited via co-combustion in a cement kiln. The SRF is produced in a single stream Mechanical–Biological Treatment plant, where bio-drying of the waste is followed by mechanical refining in order to fulfil the quality requirements by the cement kilns. Peculiar of this MBT is the fact that sorting residues are disposed in a nearby landfill, managed according to a bioreactor approach, where landfill gas is collected for electric energy recovery. A detailed mass and energy balance of the system is presented based on one year operational data, followed by its Life Cycle Assessment. Results show that the system is energetically and environmentally effective, with most of the impacts being more than compensated by the savings of materials and energy. Major role in determining such outcome is the displacement of petcoke in the cement kiln, both in terms of its fossil CO2 emissions and of its life cycle impacts, including the trans-oceanic transport. To check the robustness of the results, two sensitivity analyses are performed on the landfill gas collection efficiency and on the avoided electric energy mix.